bagus ANALISIS ALIH FUNGSI LAHAN SAWAH MENGGUNAKAN CITRA SATELIT PADA GOOGLE EARTH PRO DI DESA SAMBANGAN - Pandita, Kadek; Putra, I Wayan Krisna Eka; Wisnawa, I Gede Yudi (Universitas Pendidikan Ganesha, 2024)
Changes in the use of rice fields in Sambangan Village are accelerating as development increases every year. This research aims to identify the distribution of rice fields and the factors that cause changes in land use in Sambangan Village. The method used is quantitative descriptive. According to RSNI, land use types include gardens, settlements and rice fields. In 2009, the area of ​​rice fields reached 229.17 hectares (100%). In 2022, the area decreases to 189.48 hectares (82.74%), with 12.91 hectares (5.63%) turned into housing and 25.83 hectares (11.27%) into plantations. This change shows an increase in the need for residential land due to population growth and regional development, which reduces productive agricultural land. Factors that cause changes in land use include economic growth, urbanization, government policies, agricultural technology, and environmental conditions. Impacts include loss of natural habitat, reduced soil quality, and increased risk of natural disasters. Therefore, it is important to consider these consequences before changing land use.